Isolation and in vitro antagonistic screenings of oil palm (Elaeis guineensis Jacq.) fungal endophytes as biocontrol agents against Ganoderma boninense - Jack, Allicia (2014)
Basal stem rot (BSR) disease is the principal disease of oil palm. The main aim of present studies is to screen the efficacy of oil palm root fungal endophytes as new potential biocontrol agents of BSR disease. Oil palm seedlings were subjected to five treatments: (i) Trichoderma harzianum-infused mulch (TC); (ii) Ganoderma boninense and simultaneous application of T. harzianum mulch (GB + TC); (iii) G. boninense (GB); (iv) Glomus sp. (arbuscular mycorrhizal fungi) (AM) and, (v) no treatment as control. The results revealed that the highest number of fungal endophytes were obtained from the TC treatment with 75 isolates and the lowest, 20 isolates were from the AM treatment. However, treatment with the highest diversity index was represented by AM treatment with 14 species of endophytic fungi isolated. Overall, 225 isolates of endophytic fungi were obtained in this study and seven species were recorded as dominant namely Chaetomium trilaterale, Chaetomium gracile, Chaetomium cupreum, Penicillium janthinellum, Penicillium aculeatum, Eupenicillium javanicum and Paecilomyces sp. All isolates were screened in vitro against G. boninense (PER 71). The dual culture bioassay showed that isolates AM26, GB03 and AM23 displayed the strongest antifungal activity against PER 71 with mean PIRG value of 98.9%, 97.8% and 97.5% respectively. Only 11 isolates recorded mean percentage inhibition of radial growth (PIRG) values of > 80% and retested for in vitro antagonistic volatile organic compounds (VOCs) screening. Results from VOCs screening showed that isolates AM26, AM23, GB03 and AM17 produced inhibitory effects with average PIRG values of > 50%. AM26 and AM23 produced VOCs that retarded the growth of PER 71 after the second days of incubation with mean PIRG value of 67.5% and 64.6% respectively. Fungal molecular identification based on internal transcribed spacer (ITS) regions has confirmed that AM26, AM23 and GB03 were Daldinia eschscholzii. Present study demonstrated that D. eschscholzii had shown great antimicrobial characteristics against G. boninense in vitro. The VOCs produced by this species offers very good prospects for integrated management of BSR disease as it has the potential to be developed as an alternative to chemical fumigation. Thus, further in vivo studies should be carried out to confirm its efficacy as pathogen biocontrol agent.